A atividade do capital estrangeiro na Bovespa - Gonçalves Junior, Walter (2011)
This paper discusses the recent developments and growing importance of foreign investment in the Brazilian stock market and how its presence affects and is influenced by local dynamics. As a first finding it was detected an inclination of these agents to the positive feedback trading in asset sales; investigating if this behavior can possibly favour a more volatile environment, it was found that their purchases would mitigate the effect and its sales would operate the opposite one; furthermore, only in normal market conditions the excessive foreign demand puts pressure on the foreign prices significantly. It was found also the significant importance of foreign markets, domestic and foreign interest rates, local exchange rate and spot market liquidity in promoting additional buys from these players, as well as liquidity, exchange, net foreign direct investment and country risk in explaining its additional sales. Finally, good performances of developed markets and a descending Brazilian prime interest rate showed themselves as determinants of net inflows into the local stock market; moreover, the development of Bovespa Stock Exchange and an international crisis environment would be particularly significant in the dynamics of foreign inflows in Brazil.